Comparative therapeutic approach for anaemia in goats - Rao, Anna; Kasaralikar, Vivek R; D, Dilip Kumar; B G, Ravindra; Kulkarni, Shrikant; S C, Halmandage (Indian Journal of Veterinary Medicine, 2024)
The present study was conducted at Veterinary Clinical Complex, Veterinary College, Bidar, to know the therapeutic efficacy of various haematinics including blood transfusion in 24 anaemic goats. Selected goats were treated for endecto-parasites prior to therapeutic protocol. Detailed signalment, history, faecal, blood smear and clinical examination with recording of rectal temperature, respiration rate and heart rate were done. Moderate anaemic goats of Group IA were supplemented with ferric ammonium citrate complexorally, Group IB were tre ated with Inj iron dextran intramuscularly, severe anaemic goats of Group IIA were treated with Inj iron dextran intravenously and Group IIB with blood transfusion at the recommended dosage. Haemato bio-chemical parameters increased significantly (p ≤ 0.05) post therapy in all the four group of goats. Post therapy improvement was earlier and significant (p ≤ 0.05) with oral haematinic (Group IA) than parenteral iron (Group IB) in moderate anaemic goats and with blood transfusion (Group IIB) than parenteral iron (Group IIA) in severe anaemic goats. On comparative evaluation, it was found that oral haematinicwas more efficacious than parenteral iron in moderate anaemia, whereas blood transfusion was superior to intravenous iron in treatment of severe anaemia in goats.